Lactic Acidosis in Diabetic Population: Is Metformin Implicated? Results of a Matched Case-Control Study Performed on the Type 2 Diabetes Population of Grenoble Hospital University - Marion Lepelley; Joris Giai; Nassima Yahiaoui; Sébastien Chanoine; Céline Villier (Journal of Diabetes Research)
Introduction. To evaluate the strength of association between lactic acidosis (LA) and well-recognized risk factors for LA, particularly the weight of metformin. Methods. This study is a matched case-control analysis concerning the type 2 diabetes population from Grenoble Hospital University. Cases of LA were defined biologically with pH < 7.35 and lactates > 5 mmol/L. They were matched to 2 controls defined as type 2 diabetic inpatients who did not present a LA during the study period. We performed a conditional logistic regression. Results. We included 302 cases and 604 controls; mean age was 69.5 years (SD 11.93). Intercurrent diseases were significantly associated with LA. Chronic medical conditions had a minor impact on LA incidence, except hepatocellular dysfunction. Metformin was significantly associated with a higher LA probability in case of acute kidney injury (AKI) (OR = 1.79; p value = 0.020) but not in patients without AKI. Discussion and Conclusions. According to this study, metformin, compared to acute medical conditions, seemed not to be associated with LA in patients with type 2 diabetes; however in case of AKI, metformin may be associated with LA.